2004
DOI: 10.1089/105072504323150750
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism is Associated with Insulin Resistance in Rheumatoid Arthritis

Abstract: We investigated the prevalence of subclinical hypothyroidism and its association with insulin resistance and other cardiovascular (CV) risk factors in rheumatoid arthritis (RA). We recorded thyroid function tests, insulin resistance markers comprising the Homeostasis Model Assessment for insulin resistance (HOMA-IR), the Quantitative Insulin Sensitivity Check Index (QUICKI) and triglycerides/high-density lipoprotein (HDL) cholesterol ratios, and other CV risk factors in 126 patients with RA. Fifteen (12%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
3
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 14 publications
2
53
3
2
Order By: Relevance
“…The lower fasting insulin sensitivity assessed using the HOMA index was also found lower in a number of other studies in patients with SHO [4,10,33]. Yet, the results of other studies indicate a normal insulin sensitivity in that group of patients [34,35].…”
Section: Hypothyroidismmentioning
confidence: 71%
See 1 more Smart Citation
“…The lower fasting insulin sensitivity assessed using the HOMA index was also found lower in a number of other studies in patients with SHO [4,10,33]. Yet, the results of other studies indicate a normal insulin sensitivity in that group of patients [34,35].…”
Section: Hypothyroidismmentioning
confidence: 71%
“…However, it should be noted that in some of these studies in which insulin resistance was not found in patients with SHO, fasting hyperinsulinaemia was reported [33,36]. These observations may be interpreted as an early sign of impairment of glucose metabolism.…”
Section: Hypothyroidismmentioning
confidence: 90%
“…Some studies demonstrated that subclinical hypothyroidis leads to insulin resistance [31,32], but other studies did not observe this effect [33,34]. The reason for the differences in the obtained results may be due to different durations and degrees of subclinical hypothyroidism.…”
Section: Prace Oryginalnementioning
confidence: 92%
“…4,5 Only treatment of diabetes will not be that effective to resolve insulin resistance completely. Along with diabetes treatment, if we check and treat hypothyroidism even in subclinical stage then it will take care of its contribution to total insulin resistance.…”
Section: Introductionmentioning
confidence: 99%